ABO isoagglutinin titers in group “O” blood donors - Sadhana Mangwana; Shashi Kumar; Vivek Gangwar (Asian Journal of Transfusion Science)
BACKGROUND: High titers of anti-A and anti-B are considered to be one reason for hemolytic transfusion reactions and ABO hemolytic disease in fetus and neonates. There is no consensus for critical ABO antibody titers to guide transfusion or transplant decisions. Implementation of ABO titer measurement can favor reduction in transfusion reactions in nongroup “O” recipients. AIMS: This study aimed to understand the trend and quantification of anti-A and anti-B antibody titers in Group “O” donors in this geography. SUBJECTS AND METHODS: A prospective study was conducted in 218, Group “O” blood donors in the year 2021, during the COVID-19 pandemic. Immunoglobulin (Ig) M antibody titers were measured by hemagglutination and IgG titers by solid-phase red cell adherence. Antibody titers ≥128 for IgG and ≥64 for IgM were considered “high titers.” Epi Info 7.1 software was used for statistical analysis, with P < 0.05 significant. RESULTS: About 96.75% of blood donors were male with a median age of 33.16 ± 8.8 years. ABO antibody titers ranged from 0 to 1024. The prevalence of titers of <128 for IgG anti-A and anti-B was 79.36% and 86.24%, respectively, and 88.53% for both anti-A and anti-B IgM (<64). High IgG anti-A antibody titers were exhibited in 20.64% and anti-B titers in 13.76% of donors. None of the recipients showed any hemolytic reactions. CONCLUSIONS: The donor population showed predominance of low isoagglutinin titers. Defining critical titers will help formulate institutional guidelines on ABO-incompatible platelet transfusions and transplants. The use of automation in ABO titer assays removes interobserver variations and offers precise, reproducible, and less labor-intensive assays in resource-constrained settings.